'Uhh I'm not trying to be racist or anything': exploring an indexical field of Thai English. Issue 1 (2nd January 2022) - Jocuns, Andrew
ABSTRACT: This article explores the notions of indexical order and indexical field of Thai English based on 30 interviews conducted with students at a public university in Thailand. The analysis of these interviews examine an indexical field of Thai English where in many cases students perceive Thai English to be spoken by certain types of people, including: tour guides, restaurant workers, street vendors and the prime minister. This indexical field emerged even though many respondents had features of Thai English in their idiolect. The findings shed light on how we classify global varieties of English as the present study illustrates how the features of Thai English are not uniform, nor is the community of speakers who make up this variety. It is argued that a variety of English may be enregistered despite lacking a status of variety directly attributable to a community of speakers.